2021
DOI: 10.6007/ijarbss/v11-i7/10527
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Corporate Social Innovation (CSI)

Abstract: This paper highlights the variety of social innovation and corporate social innovation definitions, and concepts that have been proposed by scholars in the area of sociology, technological innovations and economics. However, there is no commonly agreed definition, as it depends on the multidisciplinary field, sector and country. In particular, the concept from the business perspective is still vague. This study discovered that widespread ambiguities and vagueness dominate the concept of social innovation in ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…However, the literature on CSI remains underdeveloped and immature (Benneworth & Cunha, 2015). Previous research has shown that the concept of CSI is still in its infancy (Mustapha et al, 2021;van der Have & Rubalcaba, 2016), and there has been little research on the use of social innovations as a specialized strategy to influence companies' business. The lack of empirical data on CSI and the absence of a united set of metrics to accurately reflect the breadth and scope of CSI pose significant challenges to researchers (Mihci, 2020).…”
Section: Corporate Social Innovation (Csi)mentioning
confidence: 99%
“…However, the literature on CSI remains underdeveloped and immature (Benneworth & Cunha, 2015). Previous research has shown that the concept of CSI is still in its infancy (Mustapha et al, 2021;van der Have & Rubalcaba, 2016), and there has been little research on the use of social innovations as a specialized strategy to influence companies' business. The lack of empirical data on CSI and the absence of a united set of metrics to accurately reflect the breadth and scope of CSI pose significant challenges to researchers (Mihci, 2020).…”
Section: Corporate Social Innovation (Csi)mentioning
confidence: 99%
“…By using OSI as a business model, we might contribute to the 2030 Sustainable Development Goals. However, there are other arguments for and against the idea of OSI in the business world, and this area of study is still in its infancy (Mustapha et al, 2021), some. Additionally, there are persistent arguments in the workplace about corporate social responsibility (CSR).…”
Section: Introductionmentioning
confidence: 99%